Ein fossiler semi-arider tropischer Karst auf Ithaka - Maurin, Viktor; Zötl, Josef (ERDKUNDE, 1966)
Next to the modification of karst forms by lithological conditions, climatic differentiation is most important. The literature on climatically conditioned variations is dominated by the exotic forms of the humid tropics; it is only recently that J. N. Jennings and M. M. Sweeting (1963) have steered attention back to the tropical arid and semi-arid areas. Also, thought on the remains of a palaeoclimatic karst is pursued mainly in terms of humid tropical conditions. On the northern half of Ithaca (Ionian Islands) there is a surface sloping today at 460 to 480 metres above sea level. It bevels a horizontally-bedded Cretaceous Rudiste lime stone and passes into the solution rim of the next-highest step in towers and 'woolsack' shapes. The concave grooves found on some towers and now at a height of 5,5 metres mark former surface hollows. In the course of morphogenetic investigations on Kephallinia and Ithaca the surface was dated as upper Pliocene. Based on the morphological work and palaeoclimatic investigations of D. Jaranoff (1944) and others, the interpretation is made that in this part of Ithaca, we are dealing with a fossil semi arid tropical karst, and this is very strongly supported by a comparison with recent forms of that kind in N. W. Australia.